Joseph had a little overcoat - Taback, Simms (New York : Viking, 1999)
A very old overcoat is recycled numerous times into a variety of garments.
Based on "... a Yiddish folk song..."
Keywords: Toy and movable books -- Specimens; Jews -- Folklore; Caldecott Medal; Coats -- Folklore; Toy and movable books; Folklore -- Europe, Eastern